Primary Malignant Melanoma of the Vagina: Report of Two Cases and Review of the Literature - Yavas, Guler; Oner, Irem; Yavas, Cagdas; Sen, Erdem; Karabagli, Pinar; Celik, Cetin; Ata, Ozlem (Archives of Clinical and Medical Case Reports, 2017)
Vaginal malignant melanoma is a rare form of mucosal melanoma, and accounts for only <1% of all melanomas and 1.6% of female genital tract melanomas. Due to the rarity of the disease, currently, no standard treatment protocol has been established for the treatment of vaginal melanomas. Unfortunately, vaginal melanomas are often only diagnosed at an advanced stage, and treatment options include local excision with wide margins, radical surgery, radiotherapy, chemotherapy, and immunotherapy. Despite these aggressive treatment approach, the prognosis of vaginal melanoma is poor, and the 5-year overall survival rate is 0–25%. Since patients with vaginal melanoma ultimately develop distant metastatic disease regardless of the primary treatment approach; patient preference and quality-of-life considerations are critical factors in determining initial management. Herein we report two cases of vaginal melanoma. The first case was staged as T4bN0M0 according to the American Joint Committee on Cancer (AJCC) classification system. She denied surgery therefore underwent definitive radiotherapy. The patient is on routine follow-up, and now after 13 months of the completion of the treatment, she is still free of disease. The second case was T4bN1M0 according to AJCC classification system and underwent wide local excision with vaginectomy and bilateral inguinal lymph node dissection followed by adjuvant radiotherapy and immunotherapy. She is still free of disease for 34 months. In these report we discussed the optimal treatment strategy for vaginal melanomas by the light of available literature.